The Effect of Online Brand Experience on Online Brand Loyalty Through Brand Attachment as a Mediation and Service Quality as Moderation - Dodi Ria Atmaja; Dian Indah Sari (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The global Muslim population reached 26% in 2020 and is projected to reach 34% by 2070, driving significant demand for halal tourism. Indonesia, as the country with the largest Muslim population, possesses enormous potential for Sharia tourism development, yet faces challenges including unclear regulations, limited facilities, and low public awareness of halal certification. In Aceh, only two out of 84 accommodation units have obtained halal certification despite many claiming to operate on Sharia principles. Method: This study employed a quantitative approach with explanatory and correlational research design. A sample of 600 respondents was selected using simple random sampling from star-rated hotels in Banda Aceh. Data were collected through closed questionnaires with a 1-5 Likert scale. Data analysis utilized Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using SmartPLS 4.0 software. Results: The results indicate that all branding variables—Brand Salience, Brand Meaning, Brand Response, Brand Resonance—and the Role of Government have significant positive influences on Sharia tourism development (p-value < 0.05). Brand Resonance demonstrated the strongest influence (path coefficient 0.321), followed by the Role of Government (0.289). The model showed good goodness of fit with SRMR 0.035 and NFI 0.926. Conclusion: The conclusion emphasizes that strong halal accommodation branding and government support through regulation and oversight are essential keys to positioning Aceh as a leading destination in the global halal tourism industry.